Tasfir Peshat terhafap Perkawinan Campur dari Anak-anak Allah di dalam Kejadian 6:1-4 - Jujung Rilman Tambunan; Kalis Stevanus (Sekolah Tinggi Teologi Baptis Indonesia, 2023)
This article seeks to read the meaning of mixed marriage for God's children in the text of Genesis 6:1-4 through the peshat interpretation. This interpretation approach is one of the traditional Jewish hermeneutical methods. It is hoped that with this approach, a more profound explanation can be obtained regarding the context of marriage at that time so that it also triggers and causes